2022
DOI: 10.3390/polym14122395
|View full text |Cite
|
Sign up to set email alerts
|

Edible Polymers and Secondary Bioactive Compounds for Food Packaging Applications: Antimicrobial, Mechanical, and Gas Barrier Properties

Abstract: Edible polymers such as polysaccharides, proteins, and lipids are biodegradable and biocompatible materials applied as a thin layer to the surface of food or inside the package. They enhance food quality by prolonging its shelf-life and avoiding the deterioration phenomena caused by oxidation, humidity, and microbial activity. In order to improve the biopolymer performance, antimicrobial agents and plasticizers are also included in the formulation of the main compounds utilized for edible coating packages. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 173 publications
1
25
0
1
Order By: Relevance
“…Our results revealed that the addition of annatto to cellulose acetate decreased the stiffness of the obtained nanofibers. Similar results were reported in previous studies showing a reduction in polymer stiffness as a result of adding eugenol, ginger, cinnamon, guarana, and rosemary extract (Bonilla et al, 2018;Ke et al, 2019;Moeini et al, 2022). Furthermore, the nanofiber stiffnesses obtained in our work (323 MPa and 211 MPa) presented comparable values to the electrospun matrices developed for muscle tissue engineering (Cooper et al, 2010;Riccotti et al, 2012;Luo et al, 2018;Jekins and Little, 2019).…”
Section: Figuresupporting
confidence: 91%
“…Our results revealed that the addition of annatto to cellulose acetate decreased the stiffness of the obtained nanofibers. Similar results were reported in previous studies showing a reduction in polymer stiffness as a result of adding eugenol, ginger, cinnamon, guarana, and rosemary extract (Bonilla et al, 2018;Ke et al, 2019;Moeini et al, 2022). Furthermore, the nanofiber stiffnesses obtained in our work (323 MPa and 211 MPa) presented comparable values to the electrospun matrices developed for muscle tissue engineering (Cooper et al, 2010;Riccotti et al, 2012;Luo et al, 2018;Jekins and Little, 2019).…”
Section: Figuresupporting
confidence: 91%
“…Currently, polymers obtained from natural sources are trying to replace synthetic polymers for their applications in the medical or agri-food fields. Based on the literature data regarding the matrix components used in this study, it can be considered a biodegradable polymer [ 76 , 77 ]. The edible films, enriched with essential oils, offer improved functionality and can be used for active packaging of perishable food products (meat, fish, seafood, fruits, vegetables, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This high molecular weight polysaccharide is yellowish-white and odorless, consisting of a rod-like structure with a mannose backbone linked by β-glycosidic bonds (1-4) and galactose side chains linked to the mannose backbone with an average molecular ratio of 1:2. The structure contains D-galactose units that are alternately joined via glycosidic bonds (1)(2)(3)(4)(5)(6). The polymer chain's hydroxyl groups enable the creation of various derivatives with potential industrial uses [25].…”
Section: Natural Gumsmentioning
confidence: 99%